Acción inhibitoria de la fase líquida del fango del volcán Copahue (Neuquén, Argentina) sobre la microbiota de piel, fosas nasales, intestinal y vaginal - De Michele, Daniel; Giacomino, Marta; Belderrain, Andrés; Schell, Celia María; Grenóvero, Silvia; Basualdo, Juan Ángel; Sparo, Mónica Delfina; De Luca, María Marta (Anales de Hidrología Médica, 2008)
The objective of this study was to determine the inhibitory effect of the liquid phase (FL) of Copahue Thermal Mud (Neuquen, Argentina) on skin, nostril, intestinal, and vaginal microbiota. Staphylococcus aureus, Staphylococcus epidermidis, Enterococcus faecalis and Candida albicans were used. The mud samples came from five different places of the “Sulphurous Lake”. Diffusion in Agar and Bactericidal rate tests were used to measure the FL inhibitory effect. The diffusion in Agar Test showed inhibition for S. aureus and C. albicans and no inhibition for S. epidermidis and E. faecalis. The dynamic activity study on S. aureus, E. faecalis and C. albicans showed bactericidal effect (reduction >3 log.) six hours after the exposition and growth with a 24- hours incubation period. S. epidermidis’s bactericidal effect was seen after four hours. The difference observed between the results of the diffusion test and the bactericidal inhibition test shows the low sensitivity of qualitative diffusion techniques in order to establish the sensitivity or resistance of different microorganisms in the LP. This has been the first paper that has studied the inhibitory effect of FL mud on the mentioned microorganisms.
Keywords: Peloid; Mud; Inhibitory Effect; Copahue